The Legal Status of Non-Muslims in the Shiite Fiqh and Iranian Laws (1906-2020) - Edalatnejad, Saeid, author.
1 online resource
Keywords: This work, a partial history of Iranian laws between 1906 and 2020, demonstrates that the main obstacle to improving the legal status of non-Muslims in Muslim contexts is the fiqhī opinions, which are mistakenly regarded as an integral part of the Islamic faith. It aims to clarify why and how Islamic Shiite rulings about non-Muslims shifted to the Iranian laws and how it is possible to improve the legal status of the Iranian non-Muslims under the Islamic government.